2018
DOI: 10.1155/2018/4374087
|View full text |Cite
|
Sign up to set email alerts
|

Lutein and Zeaxanthin Isomers Reduce Photoreceptor Degeneration in the Pde6brd10 Mouse Model of Retinitis Pigmentosa

Abstract: Purpose Lutein, RR-zeaxanthin, and RS-zeaxanthin (L-Z) are antioxidants which can reduce endoplasmic reticulum stress (ERS) and oxidative stress (OS), and ameliorate neurodegenerative diseases. However, their treatment effect in the Pde6brd10 (rd10) mouse model of retinitis pigmentosa (RP) and the underlying cellular mechanisms have not been studied. ERS is an important factor which causes photoreceptor apoptosis. The aim of the current project is to test the treatment effect of L-Z in rd10 mice and to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Administration of antioxidants has in some cases improved PR survival. Rs1 tm1Web homozygous females or hemizygous males fed a diet high in DHA [493] or Pde6b rd10 mice fed lutein and zeaxanthin [494] showed a significant PR preservation. Further, injections of a mixture of antioxidants-alpha tocopheral, ascorbic acid, alpha-lipoic acid, and/or Mn(III)tetrakis porphyrin-were able to slow the loss of cone/rod PRs in Pde6b rd1 [495], and Pde6b rd10 mice and in mice with a rhodopsin Q344ter mutation [492].…”
Section: Effects Of Environment On Pr Degenerationmentioning
confidence: 96%
“…Administration of antioxidants has in some cases improved PR survival. Rs1 tm1Web homozygous females or hemizygous males fed a diet high in DHA [493] or Pde6b rd10 mice fed lutein and zeaxanthin [494] showed a significant PR preservation. Further, injections of a mixture of antioxidants-alpha tocopheral, ascorbic acid, alpha-lipoic acid, and/or Mn(III)tetrakis porphyrin-were able to slow the loss of cone/rod PRs in Pde6b rd1 [495], and Pde6b rd10 mice and in mice with a rhodopsin Q344ter mutation [492].…”
Section: Effects Of Environment On Pr Degenerationmentioning
confidence: 96%
“…Among carotenoid in wolfberry, ZD accounts for 31%-56% of them (Peng et al, 2005), followed by β-cryptoxanthin monopalmitate, zeaxanthin monopalmitate, β-carotene and zeaxanthin (Inbaraj et al, 2008). The effect of zeaxanthin (with lutein) on retinal health was tested in several animals and clinical studies, and it has been shown to have a protective role (Sahin et al, 2019;Yu et al, 2018). For example, feeding rd10 mice with lutein and zeaxanthin isomers from P6 to P20 increased the survival of photoreceptors by around 60% (Yu et al, 2018).…”
Section: Zd Is a Promising Supplement To Delay Retinal Degenerationmentioning
confidence: 99%
“…The effect of zeaxanthin (with lutein) on retinal health was tested in several animals and clinical studies, and it has been shown to have a protective role (Sahin et al, 2019;Yu et al, 2018). For example, feeding rd10 mice with lutein and zeaxanthin isomers from P6 to P20 increased the survival of photoreceptors by around 60% (Yu et al, 2018). However, ZD, the di-ester form of zeaxanthin, which is the major carotenoid in wolfberry, has an advantage over zeaxanthin.…”
Section: Zd Is a Promising Supplement To Delay Retinal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the antioxidant capacity of LA, which has been argued previously, it could be a candidate for preventing the photoreceptors death. In fact, a variety of antioxidants has been tested as a treatment for RP in, both, animal [94,95,96] and human models [97,98].…”
Section: Lipoic Acid: An Antioxidant and Anti-inflammatory Moleculementioning
confidence: 99%